Performance enhancement of multicrystalline silicon solar cells and modules using double‐layered SiNx:H antireflection coatings. (21st May 2015) - Du, Guoping; Zhang, Yu; Li, Wang; Chen, Nan; Liu, Bingfa; Sun, Jie
Abstract: Silicon nitride coating deposited by the plasma‐enhanced chemical vapor deposition method is the most widely used antireflection coating for crystalline silicon solar cells. In this work, we employed double‐layered silicon nitride coating consisting of a top layer with a lower refractive index and a bottom layer (contacting the silicon wafer) with a higher refractive index for multicrystalline silicon solar cells. An optimization procedure was presented for maximizing the photovoltaic performance of the encapsulated solar cells or modules. The dependence of their photovoltaic properties on the thickness of silicon nitride coatings was carefully analyzed. Desirable thicknesses of the individual silicon nitride layers for the double‐layered coatings were calculated. In order to get statistical conclusions, we fabricated a large number of multicrystalline silicon solar cells using the standard production line for both the double‐layered and single‐layered antireflection coating types. On the cell level, the double‐layered silicon nitride antireflection coating resulted in an increase of 0.21%, absolute for the average conversion efficiency, and 1.8 mV and 0.11 mA/cm 2 for the average open‐circuit voltage and short‐circuit current density, respectively. On the module level, the cell to module power transfer factor was analyzed, and it was demonstrated that the double‐layered silicon nitride antireflection coating provided a consistent enhancement in the photovoltaic performance for multicrystalline silicon solar cell modules than the single‐layered silicon nitride coating. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Optimization was conducted for enhancing the photovoltaic performance of multicrystalline silicon solar modules using double‐layered silicon nitride antireflection coatings (ARC). On the cell level, the double‐layered ARC resulted in an increase of 0.21% absolute, 1.8 mV, and 0.11 mA/cm 2 for the average conversion efficiency ( ŋ ), open‐circuit voltage ( Voc ), and short‐circuit current density ( Jsc ), respectively. On the module level, a consistent enhancement in the cell to module power transfer factor was demonstrated for the double‐layered ARC over the single‐layered ARC.